207 Oncological outcomes of minimally invasive radical hysterectomy versus radical abdominal hysterectomy in patients with early stage cervical cancer: a multicenter retrospective analysis. (13th November 2020) - Rodriguez, J; Rauh Hain, J; Saenz, J; Isla, D; Rendón, G; Odetto, D; Martinelli, F; Villoslada, V; Zapardiel, I; Trujillo, L; Perez, M; Hernández, M; et al.
Abstract : Introduction: Recent evidence has shown adverse oncological outcomes when minimally invasive surgery is used in early stage cervical cancer. The objective of this study was to compare the 4-year disease-free survival in patients that had undergone radical hysterectomy and pelvic lymphadenectomy, either by laparoscopy or laparotomy. Methods: Multicenter, retrospective cohort study of patients diagnosed with cervical cancer stage IA1 with lymph-vascular invasion, IA2 and IB1(FIGO 2009 classification), between January 1, 2006 to December 31, 2017, at seven cancer centers from 6 countries. In the main patient-level analysis we used inverse probability of treatment weighting based on propensity score to construct a weighted cohort of women who differed only with respect to surgical approach. We estimated the hazard ratio (HR) for all-cause mortality after radical hysterectomy with weighted Cox proportional hazard models. Results: 1379 patients were included in the analysis, 681 (49.4%) patients operated by laparoscopy, and 698 (50.6%) by laparotomy. Median age was 46 (22–88) years. Median follow-up was 52.1(0.8–201.2) months for laparoscopy, and 52.6 (0.4–166.6) for laparotomy group. Women who underwent laparoscopic radical hysterectomy had inferior 4-year disease-free survival compared with laparotomy group (HR 1.64; 95% Confidence Interval 1.09–2.46). When the outcomes were compared according to preoperative tumor size, there was a higher risk of recurrence only in patients with a tumor size >2 cm operated by laparoscopy (HR= 2.26; 95% CI 1.17–4.37). Conclusions: In this retrospective multicenter study, the laparoscopic approach for early stage cervical cancer was associated with a higher risk of recurrence, compared to laparotomy.